If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5x + -8) = 88 Reorder the terms: 4(-8 + 5x) = 88 (-8 * 4 + 5x * 4) = 88 (-32 + 20x) = 88 Solving -32 + 20x = 88 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 20x = 88 + 32 Combine like terms: -32 + 32 = 0 0 + 20x = 88 + 32 20x = 88 + 32 Combine like terms: 88 + 32 = 120 20x = 120 Divide each side by '20'. x = 6 Simplifying x = 6
| -6x-3.4=3x+2.0 | | 6xy(3x^2-4y^2)= | | 4x+3.0=-4x-2.6 | | 4(2s)-3s=15 | | 5x=260 | | -4+-1t-t=2 | | -3s+4s=10 | | r=-3s | | 4p^2-29-20=0 | | 11m=44 | | 7x-2+4=10+5x | | 3x+3+9x-1=6x+12+2x | | (2p+3)(2p-4)=8 | | 4p^2-2p-20=0 | | 7x+16=3x-8 | | 8+6x=28-4x | | 5m+7m= | | 12m+7m= | | x^2-4+2=0 | | (y/14)+(9y/16)=y/20 | | 7+2a-6=-9 | | x-7=19+x^2 | | cotx=9 | | X+2-8x+12=0 | | (x+1)(x+2)(x+3)(x+4)-4=0 | | 100=x+.5x+.25x+1 | | 3x-x-10= | | 10x-15=6x-55 | | 13-8x=113-36x | | 2x+27=9x+2 | | 11-9x=103-37x | | 6x+12=7x-2x |